2020
DOI: 10.1007/s00380-020-01630-z
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac impact of arteriovenous fistulas: what tools to assess?

Abstract: The relationship between arteriovenous access flow (Qa) and cardiovascular changes is complex. Several studies have shown cardiac remodeling and symptoms of heart failure for high-flow arteriovenous fistulas (AVF). To evaluate the early cardiovascular impact of AVF. Forty-seven patients with an AVF, hospitalized for the evaluation of high-flow AVF or a pre-kidney transplant assessment were included. We collected clinical and biological data. We also collected data of the assessment by transthoracic echocardiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Fourth, coronary angiography was performed only in the minority of cases and no noninvasive verification of coronary status was repeated at the time of inclusion to this study; therefore, we cannot definitely exclude the impact of ischemic heart disease on our results. Fifth, despite the absence of significant contribution from AVF in multivariable models, it is likely that the AVF-related volume overload, more frequent in the HD subset, might have contributed to the between-group differences in cardiac function and morphology [30].…”
Section: Discussionmentioning
confidence: 98%
“…Fourth, coronary angiography was performed only in the minority of cases and no noninvasive verification of coronary status was repeated at the time of inclusion to this study; therefore, we cannot definitely exclude the impact of ischemic heart disease on our results. Fifth, despite the absence of significant contribution from AVF in multivariable models, it is likely that the AVF-related volume overload, more frequent in the HD subset, might have contributed to the between-group differences in cardiac function and morphology [30].…”
Section: Discussionmentioning
confidence: 98%
“…A cutoff value of 33% for Qa/CO allowed the detection of significant alteration in GLS indicative of myocardial dysfunction with a sensitivity of 92% and specificity of 66%. 9 Moreover, although a specific fistula flow cutoff value conferring a high risk of cardiac failure is still debated, numerous studies have shown that AVF with a blood flow exceeding 1500 ml/min are at a heightened risk.…”
Section: Avf Ligation Can Mitigate Cardiac Remodelingmentioning
confidence: 99%